2021
DOI: 10.1007/s42486-021-00063-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Human activity recognition with deep learning: overview, challenges and possibilities

Abstract: The growing use of sensor tools and the Internet of Things requires sensors to understand the applications. There are major difficulties in realistic situations, though, that can impact the efficiency of the recognition system. Recently, as the utility of deep learning in many fields has been shown, various deep approaches were researched to tackle the challenges of detection and recognition. We present in this review a sample of specialized deep learning approaches for the identification of sensor based human… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 195 publications
0
4
0
Order By: Relevance
“…Machine learning is one of the key emerging technology for processing health data for diagnosis purposes and is playing an important role in enhancing the performance of WBANs [ 239 , 240 ]. Communication networks are also benefiting from technology [ 241 ].…”
Section: Open Issuesmentioning
confidence: 99%
“…Machine learning is one of the key emerging technology for processing health data for diagnosis purposes and is playing an important role in enhancing the performance of WBANs [ 239 , 240 ]. Communication networks are also benefiting from technology [ 241 ].…”
Section: Open Issuesmentioning
confidence: 99%
“…The authors found that the decision tree algorithm outperformed other algorithms in terms of accuracy. This study [22] provides an overview of the current state of the art in deep learning for human activity recognition. The authors present a classification of deep learning models used for this task, including CNNs, RNNs, and Autoencoders, and discuss the challenges and opportunities in this field.…”
Section: Related Workmentioning
confidence: 99%
“…Besides smart surveillance, HAR has numerous applications such as video retrieval [ 4 ] and video summarization [ 5 ]. However, accurate HAR using computer vision techniques is challenging due to instantaneous transition of events in successive frames, illumination variations, different viewpoints, cluttered background, and different scaling [ 6 ]. In videos context, activity recognition relies on the collection of multiple consecutive video frames, where both spatial and temporal information need to be analysed for an individual's body movements.…”
Section: Introductionmentioning
confidence: 99%